Ownership and segment disclosure : moderating effect of competitiveness in Malaysia / Jalila Johari, Susela Selvaraj Devi and Sureshchandra Ramachandra - Johari, Jalila; Selvaraj Devi, Susela; Ramachandra, Sureshchandra (Universiti Teknologi MARA Cawangan Selangor, 2016)
This paper aims to investigate whether firm and industry level of competitiveness has had a moderating effect on the level of segment disclosure, prior to the introduction of IFRS 8 – operating segments for companies, with differing ownership structures in Malaysia. A self-constructed segment disclosure index using data was drawn from firms listed in the Malaysian stock exchange for the period of 2006 to 2008. A total of 1,752 firm-year observations were used. The results show that competitiveness, either at the firm level or industry level experienced no effect on the extent of segment disclosures during the duration of pre-IFRS 8. However, the findings suggest that accounting qualifications of audit committee members, sizes of firms, years of listing, profitability and analyst following of the firms have significantly explain the extent to which segment information was disclosed in Malaysia.